Effect of nonsurgical periodontal therapy on the level of salivary antioxidants in patients with generalized moderate-to-severe chronic periodontitis - Ferena Sayar; Roya Shariatmadar Ahmadi; Mostafa Montazeri (Tabriz University of Medical Sciences, 2019)
Background. In the course of periodontal diseases, polymorphonuclear leukocytes (PMNs) produce oxidative agents and free radicals, thus triggering oxidant-antioxidant disequilibrium in the saliva. Due to the reduction of antioxidant protective effect, oxidative stress is induced, destroying periodontal tissues. This study aimed to investigate the consequences of the non-surgical phase of periodontal therapy on the level ofsalivary antioxidantsin patients with generalized moderate-to-severe chronic periodontitis. Methods. Un-stimulated salivary samples were collected from 43 patients with generalized moderate-to-severe chronic periodontitis for 5 minutes. Clinical parameters, including clinical attachment loss (CAL), bleeding on probing (BoP) and pocket depth (PD), were recorded in each tooth and subsequently, scaling and root planing (SRP) was carried out. After four weeks, salivary samples were collected once again, and the above-mentioned clinical parameters were recorded. Following centrifugation and freezing at a temperature of -80°C, salivary samples were examined simultaneously in a single day, and the level of their antioxidants was measured with ferric reducing ability of plasma (FRAP) method using a spectrophotometer. Results. The concentration of salivary antioxidants significantly increased four weeks following the non-surgical periodontal therapy (P<0.0001). Moreover, the clinical parameters of CAL, BoP and PD showed a significant decrease in 4 weeks as well (P<0.0001). Conclusion. The level of salivary antioxidants in patients with generalized moderate to severe chronic periodontitis significantly increased after etiotropic periodontal therapy, indicating the possible beneficial influence of periodontal therapy on the level of salivary antioxidants in patients suffering from periodontitis.